Application of walnut shell ash/ZnO/K2CO3 as a new composite catalyst for biodiesel generation from Moringa oleifera oil. (1st March 2022) - Foroutan, Rauf; Peighambardoust, Seyed Jamaleddin; Mohammadi, Reza; Peighambardoust, Seyed Hadi; Ramavandi, Bahman
Graphical abstract: Highlights: Walnut shell ash (WSA) was decorated with ZnO and K2 CO3 to produce a catalyst. WSA/ZnO/K2 CO3 was applied to biodiesel generation from Moringa oleifera oil. The generated catalyst and biodiesel were physiochemically characterized. Maximum efficiency was obtained at 65 °C, time of 4 h, and catalyst mass of 4 wt%. The generated biodiesel fulfilled ASTM-D6751 and EN-14214 standards. Abstract: A novel heterogeneous catalyst based on walnut shell ash (WSA)/ZnO/K2 CO3 composite was synthesized and applied for the production of biodiesel via the transesterification process of Moringa oleifera non-edible oil. Chemical precipitation and calcination processes were used to produce the catalyst. The results showed that the specific active surface areas for free WSA, ZnO, and WSA/ZnO/K2 CO3 composite samples were 8.1, 24.1, and 1.9 m 2 .g −1, respectively. XRD and FTIR tests were confirmed the occurrence of different functional groups or compounds in the structure of the synthesized catalyst and indicated the activity potential of the catalyst. A response surface method-central composite design (RSM-CCD) was used to investigate the effect of independent variables including the temperature and time of reaction, the methanol to oil ratio, and catalyst concentration on the process efficiency. A probability value (P-value) < 0.0001 and a Fisher value (F-value) of 192.16 were obtained indicating the high capability of the proposed model. The value of C.V.% of 1.10 showed that there is a little deviation between the experimental and the predicted data by the model, which shows the high accuracy of the model. In addition, R 2 and Adj. R 2 parameters confirmed the high ability and accuracy of the model. Based on RSM-CCD results, the maximum efficiency of 97.34 % was obtained using a reaction temperature of 65 °C, a reaction time of 4 h, a catalyst content of 4 wt%, and methanol to oil ratio of 18:1. Moreover, it was shown that that the synthesized catalyst can be re-cycled for multiple usages in the biodiesel generation process. The E factor showed that the produced fuel is biocompatible. The properties of the produced biodiesel showed that it has good compliance with ASTM-D6751 and EN-14214 and can replace diesel-derived fuels as a suitable fuel source.